A novel approach to sperm selection: Nanoparticle-based purification improves quality of Angora cryopreserved buck’s semen - Alemdar, H; Tırpan, MB (Journal of the Hellenic Veterinary Medical Society, 2023)
The Aim: The aim of the study was to investigate the applicability of an up-to-date method, sperm selection with nanoparticles at different temperatures (37ºC, 21ºC, and 4ºC), on Angora buck semen. Material and Methods: Semen samples were collected from 3 Angora bucks with 7 repetitions and each sample was diluted and divided into 4 groups. Nanopurification procedure was applied by using a nanoparticle dose of 10 μg/ml to the three groups at 37ºC, 21ºC, and 4ºC while in the control group samples were cryopreserved without nanopurificiation treatment. Post-thaw motility and morphology parameters of the sperm samples were analyzed by using computer-aided sperm analysis (CASA) and fluorescein microscopy. Results: After nanopurification at 37ºC total motility, linearity (LIN) (P<0.05), curvilinear velocity (VCL), straight-line velocity (VSL), and acrosome integrity parameters (P<0.001) were higher than the control group while the semen samples nanopurified at 21ºC were superior to the control group in terms of LIN, straightness (STR) (P<0.05), VCL, VSL, average path velocity (VAP), wobble and acrosome integrity (P<0.001). There was no significant difference between the control and the 4ºC group. Conclusion: In conclusion, nanopurification procedure on buck semen was useful in terms of parameters that affect fertility and the method can be performed at 21ºC, as well as 37ºC, to adapt the procedure to field conditions;